The Influence of Atmospheric Cues on Online Impulse Buying across Product Categories: The Mediating Role of Consumer Impulsiveness - Sarah, Farah Hasan (Curtin University, 2020)
Built on “Stimulus-Organism Response (S-O-R) model”, the study investigates the influence of different atmospheric cues on online impulse buying behavior (OIBB). The study integrates consumer impulsiveness and product category as new dimensions to the existing model to address the current research gap. A cross-sectional survey on 335 customers reveals that the influence of atmospheric cues on OIBB varies across product categories, indicating clear implications for online retailers to tailor online atmospheric cues across product categories.